SEROLOGICAL STUDY FOR BL AND IBR VIRUSES IN AND AROUND BAGHDAD AREA BY ELISA. - Kh. Majeed. , A. (The Iraqi Journal of Veterinary Medicine, 1994)
Two hundred and eight six blood samples were collected from cross bred cows and calves at several rearing plants in and around Baghdad arca. Such samples were screened for the presence and spread of B.L and IBR disease. ELISA we used for all samples check for the Presence of specific anti Bl. and TBR viral antibodies. Results indicated the paresence of such antibodies in percentages of 7.1% ((from atotal of 198 samples)) for BL virus and 11.5% ((from atotal of 164 sample)) for TBR virus. Results also showed variable infection rates among different plants under survey.